UNDERSTANDING NEUROSCIENCE, HOW THE BRAIN WORKS, AND THE IMPLICATION ON GRAMMAR TEACHING AND LEARNING - Astutik, Indri; Jonathans, Peggy Magdalena; Ratri, Devinta Puspita; Devanti, Yeni Mardiyana (ELLITE, 2023)
One of the human attributes is the ability to process language.  Over the last few decades, we have learned a lot more about its neurological foundation that specific linguistic functions are believed to be supported by various brain’s sections in left and right hemispheres. However, studies have shown that language comprehension and grammar depend on other areas of the brain outside the so-called Broca's region, which corresponds to Brodmann areas 44 and 45. It has been linked to an expanded brain activity including BA44, BA45, and BA47, the anterior insula (BA13), the mesial part of the supplementary motor area (the lateral expansion of BA6), and the bottom layer of the forebrain. Studies have also exposed the brain’s memory systems in language learning, storage, and usage, which are called as declarative/procedural memory systems. Further, studies have unveiled that these declarative/procedural memory systems can be enhanced through interventions. Thus, understanding these issues is advantageous for language teachers/instructors to know how the brain works in learning a language and its grammar, which is vital to have effective teaching and learning. Such understanding may lead teachers to develop their syllabus and materials, select strategies and methods, and design various class activities that result in effective learning.